PENGARUH INTEGRASI KOMUNIKASI PADA KEPUTUSAN PEMBELIAN KONSUMEN DI PT BERLIAN TANGGUH SEJAHTERA - VIVIENTY WY; HARNANDO TANTO (JURNAL ILMIAH MAKSITEK, 2019)
PT Berlian Tangguh Sejahtera is one of the companies engaged in the delivery of expedition services in the city of Medan, where in carrying out its operational activities this company has not implemented effective communication integration to consumers, so they have not been maximal in implementing consumer desires regarding what services to provide. consumers want when the company provides information about the service system that is applied when delivering goods, where the service system provided is still not in accordance with customer expectations. As a result, many customers are disappointed with the services provided, where the services provided are still not in accordance with the wishes and expectations of consumers.This study aims to determine whether the integration of communication about the product can influence consumer decisions to buy products and expedition services at PT Berlian Tangguh Sejahtera. Data analysis in this study used validity and reliability tests, simple linear regression analysis and hypothesis testing, such as the coefficient of determination and t test, where the population in this study were consumers of PT Berlian Tangguh Sejahtera which amounted to 1500 people, while the sampling method in this study used accidental sampling method which is calculated using the slovin formula which in the end the number of samples that were successfully drawn were 45 consumers. The results of this study state that the communication integration variable has a significant effect on the purchasing decision variables in using expedition products and services at PT Berlian Tangguh Sejahtera Medan.